Genome-wide association and Mendelian randomisation analysis provide insights into the pathogenesis of heart failure - Sonia Shah (Nature Portfolio, 2020)
Heart failure is a complex syndrome that is associated with many different underlying risk factors. Here, to increase power, the authors jointly analyse cases of heart failure of different aetiologies in a genome-wide association study and identify 11 loci of which ten had not been previously reported.